Development of Technology-Based Education Curriculum as a Form of Sustainable Education - Jaalussalam, Ejen; Pertiwi, Dian; Hidayat, Ishak; Romlah, Romlah (Journal of English Language and Education, 2025)
The development of the times goes hand in hand with the development of technology and science, which automatically influences the world of education. Technology and education have a close relationship. In Indonesia, technology has been integrated into the curriculum system. The Indonesian government still implements an independent curriculum with the use of technology. A technology-appropriate and oriented curriculum system not only improves the quality of education but also serves as a catalyst for sustainable social and economic transformation. This is an interesting area to research, particularly in understanding the value of technology use in the educational curriculum. The research employs a descriptive qualitative method. The study, based on literature review, utilizes secondary data from existing studies. The research findings indicate that a curriculum system based on Information and Communication Technology (ICT) can create supportive learning environments. This is manifested in several ways, including engaging or interactive learning, more realistic learning experiences, more effective and efficient learning management, encouragement of independent learning, improved learning quality, flexible learning processes, and fostering positive responses in learning.